THE ROLE OF VILLAGE FUNDS IN VILLAGE FINANCIAL INDEPENDENCE (A Case Study in Jombang Regency) - Susanto, Arys Wahyu; Khusaini, Moh.; Badriyah, Nurul (Journal of Indonesian Applied Economics, 2021)
This study aimed to analyze the factors that affect village original income as a component of village financial independence and evaluate the role of village funds for community empowerment in strengthening the influence of VoE on village original income in Jombang Regency. This study used the Moderated Regression analytical method with the Robust Least Square method to test the cross-sectional data provided by Siskeudes of Jombang Regency of 2019. The analysis results showed that village asset utilization affects village original income positively and significantly. Furthermore, it also confirmed the moderating role of the village fund for community empowerment in strengthening the influence of Village-owned Enterprise (VoE) on village original income. These findings indicated that the allocation of village funds to targeted community cmpowerment activities has encouraged the role of VoE in increasing village original income.